Pengembangan Modul Teknik Vokal Berbantuan Tutorial Online Pada Pembelajaran Seni Budaya Jenjang SMA - Kristiana Apresia; Trisakti Trisakti; Setyo Yanuartuti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
The study aims to develop an online tutorial vocal module as a School’s Electric Book (BSE) on musical arts subjects in particular. Test design applied a one-group pretest-posttest design. Research methods use quantitative. Development uses 4D (define, design, devlopment and dissemination). Validation a product and products include validation of language, validation of content experts and grapholographers. The quality of the module is the eligibility of languages 81,25%, the feasibility of content of the material 84,37% and the eigibility graphic of 80%. The result of the effectiveness module is ttable = 9,36 ˃ tcount = 1,96 which means the process of mocket technique full-free tutorial is effective for use in the learning process. the results are reinforced by interviews, ie 82% of self-confidence students increases, 82% student learning motivation increase, 79% students are easy to explore material, 82% of excellent students understanding material, 88% learning objectives clarifying the final result and 82% of the full-free vocal module tutorial technique great opportunities for students to study vocal technique